KAJIAN KARAKTERISTIK PERILAKU KEWIRAUSAHAAN DAN KECENDERUNGAN BERMIGRASI PEDAGANG SAYURAN DI KOTA DENPASAR - Arisena, Gede Mekse Korri; Darmawan, Dwi Putra (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Vegetable traders with operational time in the afternoon until evening, of course, have certain behaviors in Entrepreneurship and make the decision to migrate from the area of ??origin that is interesting to study. The purpose of this study was to analyze the characteristics, entrepreneurial behavior and trends of migrating Vegetable traders in Ubung Kaja Village. This research was conducted in the village of Ubung Kaja. The research location was chosen intentionally (purposive sampling) considering that Ubung Kaja Village is an area where most of the area is a residential / residential location in North Denpasar District and North Denpasar District is a densely populated area in Denpasar City. The research design carried out was a survey method. Data collection is used by direct observation and interviews. The data obtained were analyzed by descriptive analysis, logistic regression and SEM-PLS. Vegetable traders migrate from the area of ??origin to the village of Ubung Kaja (overseas areas) influenced by age of income, marital status, asset ownership and employment in the area of ??origin. The analysis results obtained entrepreneurial entrepreneurial behavior included in both categories.